The Impact Of Compensation And Work Motivation On The Performance Of Outsourcing Security Employees At PT. Sasana Duta Millenia - Muhammad bagus Yoga hutama; Sulastri Irbayuni (Cita konsultindo, 2024)
This research aims to determine the influence of compensation, work motivation and performance on outsourced security employees at PT. Millennia Ambassador Gym. This type of research is quantitative research using the Smart PLS software analysis tool. The population in this study was 70 employees and the sampling technique in this study used a saturated sample so it took the entire population. Data collection was carried out using interview techniques, observation and distributing questionnaires. Data testing techniques include validity and reliability tests, R-Square and bootstrapping hypothesis testing. Based on the research results, it can be concluded that compensation has an insignificant positive effect and motivation has a significant positive effect on the performance of outsourcing security employees.PT. Sasana Duta Millenia